P95 Preliminary Findings on Patient Satisfaction with Telepsychiatry – A Systematic Review. (8th April 2021) - Tokell, Marisa; Lin, Chung M A; Dave, Subodh; Abraham, Seri; Ramkisson, Roshelle; Mahalingappa, Sridevi S; Pillai, Anilkumar S; Matheiken, Shevonne; Iliani, Yaara Z; McNally, Rosalind; Bamrah, J S; Tokell, Marisa
Abstract: Introduction: During the COVID-19 pandemic, mental health services have been presented with the unique challenge of providing effective and safe patient care whilst maintaining safety regulations. Telepsychiatry has emerged as a potential solution to this and is now being used across the UK to diagnose and manage mental health conditions. Evidence has shown that its effectiveness is comparable to face to face consultations, however, is much less clear regarding patient satisfaction. We therefore initiated a systematic review to establish whether patients are satisfied with tele-delivery of psychiatric care, and to identify the predictors of a positive experience with telepsychiatry. Methods: A preliminary search was performed using five databases (MEDLINE, EMBASE, Cochrane Library, CINAHL, PsycINFO), with a date restriction between 2010-2020 to reflect advances in technology over the past decade. Results: Preliminary data shows that patient views on telepsychiatric services are largely positive. Factors that arose in literature potentially affecting this include location, cost, privacy, digital literacy and technological issues including audio/video quality. Conclusion: Our study so far shows that patient views on telepsychiatry are generally positive. The review is still in process, however, we anticipate that it will only further support our preliminary findings. These findings will be used to improve patient-centred delivery and provision of telepsychiatric services. We intend to produce a checklist of factors affecting patient satisfaction and test this in a national multicentre study. We are hoping that the study results and the resulting checklist will encourage greater patient involvement in setting up and delivering telepsychiatric services.